Accelerometer use in young people with Down syndrome: A preliminary cross-validation and reliability study. Issue 4 (2nd October 2017) - Peiris, Casey L.; Cumming, Toby B.; Kramer, Sharon; Johnson, Liam; Taylor, Nicholas F.; Shields, Nora
ABSTRACT: Background Inadequate physical activity is a problem for people with Down syndrome and objective monitoring using accelerometers may be inaccurate in this population. Method This was a cross-validation and reliability study comparing two triaxial accelerometers (the SenseWear and RT3) to a criterion measure (the OxyCon Mobile) in 10 young people ( M age = 20 ± 2) with Down syndrome. A ROC curve analysis was conducted to determine intensity thresholds from RT3 activity counts. Results During self-selected pace walking, the accelerometers overestimated energy expenditure and had large limits of agreement (SenseWear: −0.5–3.6 METs; RT3: −0.2–2.7 METs). At this pace, SenseWear armband step counts were highly correlated with observed steps ( r  = .98) but underestimated steps by up to 12%. We developed RT3 thresholds that demonstrated good to excellent sensitivity and specificity in classifying physical activity intensity. Conclusions SenseWear steps and RT3 activity count thresholds can be used to monitor physical activity in young people with Down syndrome, although energy expenditure estimates should be used with caution in this population.